An Investigation on Stress Management Strategies Utilized by Health Care Providers at Kamuzu Central Hospital - Milanzi, Hanneefa A.J (Kamuzu University of Health Sciences, 2022)
Work in health care has been identified as potentially very stressful due to the constant contact with pain, disease, death and suffering for which health care professionals can Frequently provide no cure. The consequent burnout, consisting of emotional exhaustion, depersonalization of patients and a sense of low personal accomplishment, has destructive effects on morale and productivity in affected work unit. Stress management is very important in the health care profession. This is why there is a need for health care providers to develop stress management strategies in order to increase productivity in the health sector and reduce impact of stress.The aim of this study was to investigate stress management strategies utilized by health care providers at Kamuzu Central Hospital. The results of the study will be used to design the possible strategies that would be used to minimize the challenges of stress faced by health care providers. The study results also will help hospital management team to plan for measures that can reduce some of the stressors encountered by health care providers by implementing orientation programs for new graduates on how to deal with stress in the work area. Before interviewing, participants were given an explanation on the purpose of the study, the importance, method and procedure of data collection and benefits of the study. The participants were informed that there are no personal benefits and risks attached to their participation in the study. The study design was descriptive in nature. This methodology was chosen because it utilizes methods of inquiry that emphasize subjectivity and the meaning of the experience to the individual presented in thoughts, ideas, feelings, attitudes and perceptions. A sample of 15 participants (health care providers) was recruited through purposeful sampling method. Data was collected using an interview guide, designed by the researcher. Data was analyzed manually and interpreted in figures and diagram. The study findings have revealed the following stressors: pressure of work or work overload which makes health care providers give poor quality care to patients and client, lack of administrative rewards such as good salaries, in-service training or refresher courses. Therefore the main conclusion of the study is that there is need to increase knowledge of health care providers on better stress management techniques in order to increase work performance and give quality care to patients and clients.